Clathrin localization and dynamics in Aspergillus nidulans. Issue 2 (14th November 2016) - Schultzhaus, Z.; Johnson, T. B.; Shaw, B. D.
Summary: Cell growth necessitates extensive membrane remodeling events including vesicle fusion or fission, processes that are regulated by coat proteins. The hyphal cells of filamentous fungi concentrate both exocytosis and endocytosis at the apex. This investigation focuses on clathrin in Aspergillus nidulans, with the aim of understanding its role in membrane remodeling in growing hyphae. We examined clathrin heavy chain (ClaH‐GFP) which localized to three distinct subcellular structures: late Golgi ( trans ‐Golgi equivalents of filamentous fungi), which are concentrated just behind the hyphal tip but are intermittently present throughout all hyphal cells; the region of concentrated endocytosis just behind the hyphal apex (the "endocytic collar"); and small, rapidly moving puncta that were seen trafficking long distances in nearly all hyphal compartments. ClaH localized to distinct domains on late Golgi, and these clathrin "hubs" dispersed in synchrony after the late Golgi marker PH OSBP . Although clathrin was essential for growth, ClaH did not colocalize well with the endocytic patch marker fimbrin. Tests of FM4‐64 internalization and repression of ClaH corroborated the observation that clathrin does not play an important role in endocytosis in A. nidulans . A minor portion of ClaH puncta exhibited bidirectional movement, likely along microtubules, but were generally distinct from early endosomes. Abstract : Aspergillus nidulans clathrin heavy chain ClaH localizes to three distinct structures. These include a dynamic plaque at the endocytic collar, domains on the late Golgi that increasingly recruit clathrin through the Golgi lifetime before dissipating at vesiculation into post‐Golgi, and mobile puncta that travel long distances on microtubules in apical and subapical regions but are generally distinct from early endosomes.